Analysis of the Development Needs of Student Worksheet Based on Local Wisdom of Biotechnology Material at Senior High School, Kupang City - Ernawati, Ernawati; Eriyanti, Ribut Wahyu; Rofieq, Ainur; Huda, Atok Miftakhul (Universitas Labuhanbatu, 2024)
This study aims to obtain an overview of the formulation of student worksheed (called as LKPD) based on local wisdom that needs to be developed in learning the biology of conventional biotechnology materials at SMA N 5 Kupang City which is adjusted to the learning achievements and objectives. The subjects in this study were 3 teachers who taught in class X of SMAN 5 Kupang City, and 175 students were randomly drawn from all grade X students of science interest at SMA N 5 Kupang City. Research data were collected through interviews and questionnaire dissemination. The research data were analyzed in a qualitative descriptive manner. The results of the study obtained teacher and student responses including students need LKPD based on local wisdom on biotechnology material to make it easier to understand the material, In addition, in learning, teachers provide examples of the results of biotechnology based on local wisdom in the form of pictures and videos, and are presented in the form of virtual laboratories with animations to attract more students' attention, so that students are more motivated to learn which will affect learning outcomes. The biology material for class X semester that is most difficult for students to understand is biological technology innovation material, so teachers need LKPD based on local wisdom in Biotechnology material, which can help students introduce local wisdom in their respective regions so that students can easily apply it in everyday life, and to support learning, which has a positive impact on improving student learning outcomes